2009
DOI: 10.1111/j.1365-2958.2009.06877.x
|View full text |Cite
|
Sign up to set email alerts
|

The right half of the Escherichia coli replication origin is not essential for viability, but facilitates multi‐forked replication

Abstract: SummaryReplication initiation is a key event in the cell cycle of all organisms and oriC, the replication origin in Escherichia coli, serves as the prototypical model for this process. The minimal sequence required for oriC function was originally determined entirely from plasmid studies using cloned origin fragments, which have previously been shown to differ dramatically in sequence requirement from the chromosome. Using an in vivo recombineering strategy to exchange wt oriCs for mutated ones regardless of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 59 publications
(98 reference statements)
9
49
0
Order By: Relevance
“…Consistent with this, the presence of dnaA defective alleles, dnaA(Sx), suppresses the detrimental effect on DNA replication observed in mutants that have problems with the progression of forks due to the presence of defective subunits of DNA polymerase III coded by the dnaX gene (Gines-Candelaria et al, 1995;Blinkova et al, 2003;Skovgaard & Lobner-Olesen 2005). Furthermore, a lower availability of wild type DnaA protein induced by the presence of extra copies of the datA sequence alleviates replication problems in both the dnaX (Skovgaard & Lobner-Olesen, 2005) and the nrdA101 mutant (this work), whilst initiation defects caused by deletion of DnaA box R4 suppress replication elongation defects (Stepankiw et al, 2009). These observations, together with our data, are consistent with the idea that the progression of replication forks is not merely responsive to elongation factors (dNTP pools or proteins engaged in elongation) but also to the number of forks running along the chromosome.…”
Section: By Deleting the Dars Sequencementioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with this, the presence of dnaA defective alleles, dnaA(Sx), suppresses the detrimental effect on DNA replication observed in mutants that have problems with the progression of forks due to the presence of defective subunits of DNA polymerase III coded by the dnaX gene (Gines-Candelaria et al, 1995;Blinkova et al, 2003;Skovgaard & Lobner-Olesen 2005). Furthermore, a lower availability of wild type DnaA protein induced by the presence of extra copies of the datA sequence alleviates replication problems in both the dnaX (Skovgaard & Lobner-Olesen, 2005) and the nrdA101 mutant (this work), whilst initiation defects caused by deletion of DnaA box R4 suppress replication elongation defects (Stepankiw et al, 2009). These observations, together with our data, are consistent with the idea that the progression of replication forks is not merely responsive to elongation factors (dNTP pools or proteins engaged in elongation) but also to the number of forks running along the chromosome.…”
Section: By Deleting the Dars Sequencementioning
confidence: 87%
“…In addition, the growth of cells in poor carbon source media is not known to affect nrdAB gene expression, and a decrease in replication rate in wild type cells has been observed under poor media conditions (Michelsen et al, 2003). Furthermore, it has been reported that deletion of DnaA box R4 suppresses replication elongation defects in gyrB mutant strains as a consequence of the lowering of initiation frequency (Stepankiw et al, 2009) indicating that no transcriptional factor is required to increase the replication rate. Hence the first proposition, in which faster replication forks are responsible for there being fewer forks, is difficult to justify.…”
Section: The Number Of Replication Rounds In the Chromosome Limits Thmentioning
confidence: 98%
“…A recent finding established that the right half of the DARDnaA sub-complex is important for stimulating DnaB helicase loading 30 , while the DUE flanking left half produces a DnaA-oriC sub-complex competent in DUE unwinding and DnaA-DnaC assisted loading of helicase protein DnaB onto single stranded DUE 30 . Interestingly, it has been observed that deletion of the right half of E. coli oriC does not affect function of the origin present in bacterial cells growing on minimal media 36 . This is due to the fact that the time needed for the completion of chromosomal replication is shorter than the cell generation time 36 .…”
Section: Formation Of Orc and Pre-rc Structures At Escherichia Coli Oricmentioning
confidence: 99%
“…Interestingly, it has been observed that deletion of the right half of E. coli oriC does not affect function of the origin present in bacterial cells growing on minimal media 36 . This is due to the fact that the time needed for the completion of chromosomal replication is shorter than the cell generation time 36 . However in rich media, the generation time of fast growing cells is approximately one third to the time required to complete the replication process and therefore the requirement of a full length oriC to support initiation on a multi-forked chromosome 36 .…”
Section: Formation Of Orc and Pre-rc Structures At Escherichia Coli Oricmentioning
confidence: 99%
See 1 more Smart Citation